Novel protein editing technologies to probe cellular damage - Poh, AWJ (2023)
Proteins are often extensively modified after translation, resulting in chemical space and protein functional states that are not bound by the ‘central dogma’. This thesis aims to develop chemical tools to precisely edit proteins in order to address important questions regarding their roles in regulating normal cellular functions and disease states. Chapter 1 summarises the current literature on protein labelling strategies for observing and probing proteins in complex biological systems, with a particular focus on the methodologies used to install a radioactive isotope onto proteins for time-resolved PET imaging. Chapter 2 describes a light-driven, radical-mediated reaction that enables the site-specific introduction of a near-zero-size, bioisosteric fluorine-18 label onto proteins. The methodology also allows for the radiolabelling of proteins with atomic-level precision, by installing a prosthetic-free, 18F-labelled lysine side chain at a pre-defined site. This creates what we call a ‘radioactive equivalent’ protein, whereby the only perturbation to the native structure is the substitution of a single hydrogen atom for fluorine-18. In the subsequent chapters, we demonstrate the broad potential of our near-zero-size protein radiolabelling method for the functional study of markers associated with disease and damage on a whole organism level. In Chapter 3, we investigate the rapid proteolysis of free histones in circulation, the cytotoxic effects induced by extracellular histones and their underappreciated ability to enter cells and broadly incorporate into chromatin. In Chapter 4, we demonstrate, to the best of our knowledge, the first real-time, dynamic tracking of neurofilament light chain (NfL) – an intrinsically disordered and aggregation-prone protein that is a putative blood-based marker for neurodegeneration – in the circulatory system of a living organism. This platform therefore now sets the stage for the unambiguous mapping of the behaviour of NfL (and its radio-metabolites) without perturbing the native assembly of this structurally dynamic protein.